2022
DOI: 10.1136/jitc-2021-003078
|View full text |Cite
|
Sign up to set email alerts
|

B cells imprint adoptively transferred CD8+T cells with enhanced tumor immunity

Abstract: BackgroundAdoptive T cell transfer (ACT) therapy improves outcomes in patients with advanced malignancies, yet many individuals relapse due to the infusion of T cells with poor function or persistence. Toll-like receptor (TLR) agonists can invigorate antitumor T cell responses when administered directly to patients, but these responses often coincide with toxicities. We posited that TLR agonists could be repurposed ex vivo to condition T cells with remarkable potency in vivo, circumventing TLR-related toxicity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Here, we demonstrated this in the context of immunotherapy, showing that B cells activated T cells in vitro and in situ at the tumor in an MHC-dependent and tumor antigen–specific manner. These activated T cells did not acquire a signature of low CD39, high ICOS, and IL-2 receptor α, as was observed in a T cell transfer study where CpG-activated B cells were used for T cell expansion ( 41 ), perhaps due to differences in our experimental procedure. We did not specifically evaluate T cell activation by other immune cells in the LN, but T cell activation in the absence of B cells was minimal.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Here, we demonstrated this in the context of immunotherapy, showing that B cells activated T cells in vitro and in situ at the tumor in an MHC-dependent and tumor antigen–specific manner. These activated T cells did not acquire a signature of low CD39, high ICOS, and IL-2 receptor α, as was observed in a T cell transfer study where CpG-activated B cells were used for T cell expansion ( 41 ), perhaps due to differences in our experimental procedure. We did not specifically evaluate T cell activation by other immune cells in the LN, but T cell activation in the absence of B cells was minimal.…”
Section: Discussionmentioning
confidence: 69%
“…These activated T cells also had increased expression of other activation markers, including CD86 and CD134, but not negative immunoregulatory receptors and activation markers such as PD1, GITR, CD39, ICOS, CD25, or CD80 (fig. S12, B and C), which are also associated with recent antigen encounter and prolonged persistence in vivo ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…In lung cancer with a more advanced stage, the fractions of PD-1 + CD39 + CD8 + T cells tend to be higher ( 51 ). PTC patients with PD-1 - CD39 + CD103 + CD8 + T cells had decreased B cells and mDC ( Figure 6A ), which are essential for CD8 + T-cell activation and antitumor response ( 52 , 53 ). In addition, our research showed that CD8 + T cells in these patients were also in a state of impaired function with low expressions of cytotoxic molecules and perforin, which is critical for antitumor immunity ( 46 ) ( Figure 6B ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one study demonstrated that ex vivo expansion of CD8 T cells for adoptive T cell transfer was achieved using TLR-activated B cells. CD8 T cells acquired a unique IL-2Rα high ICOS high CD39 low phenotype and an altered metabolic profile, all dependent on the B cells present in the culture ( 52 ). Further evidence that B cells play a positive role in cancer control is derived from mouse models.…”
Section: Antitumoral Immunitymentioning
confidence: 99%
“…However, these B cells lack the capacity to induce CD8 memory T cells compared to dendritic cell (DC) immunization with a decreased expression of the transcription factors Bcl-6 in CD8 effector cells after CD40-B cell immunization compared to DC ( 67 ). In a mouse model of anti-tumor immunity, the TLR9 agonist CpG has been shown to enhance the CD8 T cell response in vitro , in a B cell and contact-dependent manner, resulting in an improved tumor growth control and a higher mouse survival ( 52 ). Tumor-specific murine CD8 T cells [derived from splenocytes of plem-1 T cell receptor (TCR) transgenic mice] were conditioned in vitro using TLR9 - activated B – cells.…”
Section: Mechanistic Understanding Of Crosstalk Between B Cells – Cd8...mentioning
confidence: 99%